IDENTITAS KELUARGA KRISTIANI DI HADAPAN BUDAYA KONSUMERISME - Dionius Bismoko Mahamboro (Jurnal Orientasi Baru, 2016)
In this article I explore the notion of "domestic church" as identity for the christian families. One important character of christian family is found here, i. e. counter-culture as way of being in the society. In our present society which is marked by consumerism, how could christian families unfold and develop their identity as "domestic church"? This article tries to answer this question by proposing some practices that can be considered as alternative culture.